“The Friend Who Trusted Himself to You”: Networks of Recommendation among the Central Medieval Religious Elite - Rachael Haslam (Journal of Historical Network Research)
Eleventh and twelfth-century letters of recommendation are indicators of elite religious networks in Western Europe. While reference letters are a relatively transhistorical resource, those surviving from the Middle Ages are often overlooked. This article considers a network dataset derived from over one hundred central medieval letters of recommendation, which reveals a complex set of consciously created ego networks, used to create and advance careers. Visualizations of these networks show that the elite religious sphere of recommendation was not one dense network but a series of distinct, overlapping ones. The article explores the benefits of recommendation networks and their structures for both the intended beneficiary and those writing and receiving the letters. Some individuals used the letters to influence educational trends. In contrast, others received and recommended those who would be useful for specific tasks and still others only recommended people they knew well. Despite these contextual differences, the themes of reputation and exclusion permeate across all the revealed networks. Offering fresh perspectives on the networks of individuals such as St Anselm, St Bernard of Clairvaux and St Thomas Becket and considering the social consequences of reliance on networking, the article demonstrates the value of a network approach to the study of medieval epistolography.